Teachers' beliefs about inclusive education: a phenomenological study. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2019)
INTRODUCTION: This work seeks to understand and interpret teachers ‘ beliefs about educational inclusion from experienced experiences. METHODS: This study is qualitative, descriptive, phenome-nological and interpretative. The instrument used was a semi-structured interview made to 30 teach-ers. RESULTS:The beliefs related to the context and the subject. Four subcategories are born: the notion represents concepts of educational inclusion. The curriculum covers the process, development and results of the CHIRP. The experience belongs to the working context and the time it has worked with people with disabilities, the training corresponds to the professional education of the teacher. ANALYSIS AND DISCUSSION:Beliefs are understood as all those conditions of the different envi-ronments that constitute the individual. The teacher’s discourse on the meaning it gives to the concept of educational inclusion, with respect to the Recognition of diversity in the school context. In the face of inclusion it must identify and respond to the needs of all students through greater participation in their entire context, reducing exclusion. CONCLUSIONS: Knowing the beliefs that teachers have  about inclusive education is really important because they contribute to the practices they perform in classrooms, resulting in an effective, assertive or negative process for inclusive education.
Keywords: Beliefs; Educational Inclusion; Teachers; Education; Disability